Diseño y construcción de un remolque de doble eje con articulación delantera - Cardona, Jaime Roberto (2010)
This document is about the design and construction of a two-axle trailer with three doors, uncovered and provided of front articulation, the trailer is designed for 2 tons of load capacity, built with metal structures selected according to the typical calculations required for this type of constructions. For its manufacture new materials were used except for the rear shaft for the set of wheels of the trailer where a differential gear with load capacity of 2,5 tons was adapted, the front shaft is built with a steel pipe of Schedule 40 because the design does not allow another differential gear. For the design work, construction manuals for materials were used, in order to perform strength of materials calculations. This trailer is built with UPN structural shapes which are hot rolled material; this material was selected for its composition itself as it has the right characteristics to withstand static and dynamic loads. Especially this material was used for the base of the trailer. The structure of the trailer has a special design on the front axle of the wheels to have the ability to rotate 15 degrees to the left and right in order to facilitate the rolling in the curves of the routes. The idea of building the trailer came from the Master Edwin Tamayo, who is the director of the Institute of Technology at ESPOL who manages an agreement ESPOLAMAZONÍA in the province of Pastaza, agreement that carries out a project of cultivation of plants that are in danger of extinction and this is the need to build a trailer to transport agricultural products to the working areas, such as plants, fertilizers and tools needed for development work.